Vertebrate Paleontology in Central America: 30 years of progress - Lucas, Spencer G. (2014)
Vertebrate paleontology began in Central America in 1858 with the first published records, but the last 30 years have seen remarkable advances. These advances range from new localities, to new taxa to new analyses of diverse data. Central American vertebrate fossils represent all of the major taxonomic groups of vertebrates—fishes, amphibians, reptiles (especially turtles), birds and mammals (mostly xenarthrans, carnivores and ungulates)—but coverage is very uneven, with many groups (especially small vertebrates) poorly represented. The vertebrate fossils of Central America have long played an important role in understanding the great American biotic interchange. New data and analyses identify a Miocene Central American peninsula that extended from Guatemala to Panama, and suggest the possibility of a Central American province of vertebrate endemism and evolution. The Central American record of vertebrate fossils needs augmentation, especially of microvertebrate fossils, and a more detailed chronological framework to enhance our current understanding of vertebrate evolution and biogeography in the New World